Beyond ‘BRICS’: ten theses on South–South cooperation in the twenty-first century - Muhr, Thomas (Taylor & Francis, 2016)
Grounded in a review of past and present academic South–South cooperation literatures, this article advances ten theses that problematise empirical, theoretical, conceptual and methodological issues essential to discussions of South–South cooperation in the 21st century. This endeavour is motivated by the perceived undermining, especially in the contemporary Anglophone academic South–South cooperation literature, of the emancipatory potential historically associated with South–South cooperation. By drawing on the interventionist South–South cooperation agendas of ‘left’-leaning Latin America-Caribbean governments, the article seeks to establish a dialogue between social science theories and less ‘visible’ analyses from academic (semi)peripheries. The ten theses culminate in an exploration of the potential of South–South cooperation to promote ‘alternative’ development.